2016
DOI: 10.1016/j.atmosenv.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particle size as a tracer for aircraft turbine emissions

Abstract: Ultrafine particle number (UFPN) and size distributions, black carbon, and nitrogen dioxide concentrations were measured downwind of two of the busiest airports in the world, Los Angeles International Airport (LAX) and Hartsfield-Jackson International Airport (ATL - Atlanta, GA) using a mobile monitoring platform. Transects were located between 5 km and 10 km from the ATL and LAX airports. In addition, measurements were taken at 43 additional urban neighborhood locations in each city and on freeways. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…5,6 Aviation nvPM emissions absorb solar radiation, affect cloud formation, and deteriorate air quality at airports and in nearby communities. 3,4,[7][8][9][10][11] Due to their potential health and climate impacts, various research programs have focused on characterization of particle emissions from aircraft engines, development of measurement techniques and predictive models for estimating aviation nvPM emissions. [12][13][14][15][16][17] Recent research has been motivated also by the development of a certification standard for nvPM emissions of new commercial aircraft turbine engines.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Aviation nvPM emissions absorb solar radiation, affect cloud formation, and deteriorate air quality at airports and in nearby communities. 3,4,[7][8][9][10][11] Due to their potential health and climate impacts, various research programs have focused on characterization of particle emissions from aircraft engines, development of measurement techniques and predictive models for estimating aviation nvPM emissions. [12][13][14][15][16][17] Recent research has been motivated also by the development of a certification standard for nvPM emissions of new commercial aircraft turbine engines.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified civil and military aircraft activity as a potential source of particulate matter emission near airport zones [1][2][3][4][5][6][7]. In particular, it was highlighted that aircraft activity could contribute to increasing the levels of fine and ultrafine particles (UFPs) in the surrounding environment, with potential effects on the health of the population in the vicinity of the emission source [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the smaller UFPs that are transported downward from this elevated source spend even less time interacting with potentially higher concentrations of existing particles that occur at ground level, such as those found on or near major roadways. It is therefore not surprising that the typical size of these UFPs in the downwind footprint shown in Figure 2 are typically very small 10-30 nm, indicating minimal coagulation losses (Hudda and Fruin 2016;Hudda et al 2014;Riley et al 2016;Shirmohammadi et al 2016). Furthermore, due to the consistency of daytime onshore breeze directions at LAX, the location of elevated, ground-level UFPs concentrations downwind and to the east of LAX is very stable (Hudda and Fruin 2016;Hudda et al 2014), producing relatively large contrasts in concentrations between residences inside the area of impact in comparison with those located outside.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report adverse air quality impacts from landing jets over large areas downwind of major airports (Hudda et al , 2018(Hudda et al , 2014Keuken et al 2015;Masiol et al 2017bMasiol et al , 2017aRiley et al 2016). For example, jets approaching Los Angeles International Airport (LAX) in Los Angeles, California, produce ground-level UFP concentrations more than twice the nearby ambient levels at distances up to 16 km away from the airport (Hudda et al 2014).…”
Section: Introductionmentioning
confidence: 99%